Evolution of South Atlantic density and chemical stratification across the last deglaciation - Roberts, Jenny; Gottschalk, Julia; Skinner, Luke C.; Peck, Victoria L.; Kender, Sev; Elderfield, Henry; Waelbroeck, Claire; Vazquez Riveiros, Natalia; Hodell, David A. (National Academy of Sciences, 2016)
Explanations of the glacial-interglacial variations in atmospher¬ic pCO2 invoke a significant role for the deep ocean in the stor¬age of CO2. Deep ocean density stratification has been pro¬posed as a mechanism to promote the storage of CO2 in the deep ocean during glacial times. A wealth of proxy data sup¬ports the presence of a "chemical divide" between intermedi¬ate and deep water in the glacial Atlantic Ocean, which indi¬rectly points to an increase in deep ocean density stratifica¬tion. However, direct observational evidence of changes in the primary controls of ocean density stratification, i.e. tempera¬ture and salinity, remain scarce. Here, we use Mg/Ca-derived seawater temperature and salinity estimates determined from temperature-corrected δ18O measurements on the benthic foraminifer Uvigerina spp. from deep and intermediate water-depth marine sediment cores to reconstruct the changes in density of sub-Antarctic South Atlantic water masses over the last deglaciation (i.e. 22-2 ka before present). We find that a major breakdown in the physical density stratification signifi¬cantly lags the breakdown of the deep-intermediate chemical divide, as indicated by the chemical tracers of benthic foramin¬ifer δ13C and foraminifer/coral 14C. Our results indicate that chemical destratification likely resulted in the first rise in at¬mospheric pCO2, whereas the density destratification of the deep South Atlantic lags the second rise in atmospheric pCO2 during the late deglacial period. Our findings emphasise that the physical and chemical destratification of the ocean are not be as tightly coupled as generally assumed.